Letter from the Editor - Ashley A Humphrey (International Journal of Nuclear Security, 2022)
It is vital for women to share their experiences with others; it shrinks the distances among us, creating stronger bonds. It builds camaraderie and community. It is also vital for women to document and share their journey so others can see tangible progress and use it as a tool in their own right. So, here is my story, my confession, about being editorial liaison for the IJNS Special Issue on Women in Nuclear Security.